The welfare effects of promotional fees - Mateusz Mysliwski; Fabio M. Sanches; Daniel Silva Junior; Sorawoot Srisuma (Centre for Microdata Methods and Practice (cemmap), 2020)
Manufacturers frequently pay fees to supermarkets when they temporarily reduce prices of their products. These funds are used by supermarkets to cover the costs of promotional campaigns and to compensate reductions in markups during promotions. Anecdotal evidence suggests that these fees are sizeable and have important consequences for firms and consumers, but little is known about them quantitatively. This paper develops a dynamic game-theoretic model where multiproduct firms compete in prices and pay a cost every time they lower prices. We use the model to study pricing behaviour in the UK butter and margarine market. The magnitudes of promotional fees are then structurally estimated as price adjustment costs. Our study produces two important conclusions. First, we find that costs firms pay to lower prices are substantial and represent between 24-34% of manufacturers' net margins. Second, our model predicts that the removal of these costs reduces persistence in prices, increases firms' profits but has little effect on consumer surplus.
Keywords: C57; L11; L13; L66; 330; dynamic oligopoly; adjustment costs; price promotions; dynamic games estimation